Hume's ‘manifest contradictions’ - Kail, PJE (Cambridge University Press, 2016)
This paper examines Hume’s ‘Title Principle’ (TP) and its role in a response to one of the ‘manifest contradictions’ he identifies in the conclusion to Book I of A Treatise on Human Nature. This ‘contradiction’ is a tension between two ‘equally natural and necessary’ principles of the imagination, our causal inferences and our propensity to believe in the continued and distinct existence of objects. The problem is that the consistent application of causal reason undercuts any grounds with have for the belief in continued and distinct existence, and yet that belief is as ‘natural and necessary’ as our propensity to infer effects from causes. The TP appears to offer a way to resolve this ‘contradiction’. It states Where reason is lively, and mixes itself with some propensity, it ought to be assented to. Where it does not, it never can have any title to operate upon us.’ (T 1.4.7.11; SBN 270) In brief, if it can be shown that the causal inferences that undermine the belief in external world are not ‘lively’ nor mixed with some propensity’ then we have grounds for think that they have no normative authority (they have no ‘title to operate on us). This is in part a response to another ‘manifest contradiction’, namely the apparently self-undermining nature of reason. In this paper I examine the nature and grounds of the TP and its relation to these ‘manifest contradictions’.